2020
DOI: 10.1007/s11663-020-01795-y
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Investigation on the Electrochemical Behavior of CaO and Al2O3 in the ESR Slags

Abstract: Field structures including electromagnetic, concentration of ions, and flow fields in an ESR-like process composed of a graphite crucible containing a molten slag, air, and an iron electrode are computed. Both CaF 2-(mass pct 2) CaO and CaF 2-(mass pct 2) Al 2 O 3 slags are examined. Tertiary current distribution is calculated. Therefore, polarization overpotential and Faradic reactions at metal-slag interface are considered using Tafel law, whereas transport of ions in the bulk of slag is determined through N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…( 9) through Eq. ( 13) as listed in Table 1, are utilized to determine electric current density field in the slag considering tertiary current distribution [31]. The conservation of electric current density, Eq.…”
Section: Governing Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…( 9) through Eq. ( 13) as listed in Table 1, are utilized to determine electric current density field in the slag considering tertiary current distribution [31]. The conservation of electric current density, Eq.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Boundary conditions of electric potential and concentration of ions are interdependent [31]. The total mass flux of non-reacting ions (F À ; O 2À ) is zero at all boundaries enclosing the slag.…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…15) Many studies have reported the precipitation and removal behaviors of inclusions during solidification of steel. [16][17][18][19][20] A variety of techniques have been employed to remove inclusions from alloys, including vacuum induction melting (VIM), 21,22) elctroslag remelting (ESR), [23][24][25] Vacuum arc remelting (VAR), [26][27][28] Electron beam melting (EBM), 29,30) Hydrogen plasma arc melting (HPAM) 31,32) and double-melting or triple-melting processes. 33) Although most of the inclusions can be removed by these methods, there are drawbacks to these processes, such as the solidification defects, high energy consumption, time-consuming, and losses of high vapor pressure alloying elements.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] However, improper melting parameters may result in metallurgical defects, such as macrosegregation, porosities, and beta flecks. [4][5][6] Due to the high temperature of the smelting process, the experimental study was under restriction. The modeling study of the VAR process was used to obtain the optimal parameters for improving the quality of the ingot.Kondrashov et al [7] developed a simple heat model of the VAR process neglecting the magnetohydrodynamic phenomena in the molten pool.…”
mentioning
confidence: 99%